Idea of natural inequality and other essays - Beteille, Andre (Delhi, 1983)
The essays in this volume deal with various aspects of inequality with special reference to contemporary India but has been viewed in a comparative perspective. They deal with different forms and dimensions of inequality and with alternative conceptions of equality.
Keywords: Social classes-India